P-80 Using project ECHO™ to support comprehensive person-centred carer assessment and support in hospices. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Diffin, Janet; Ewing, Gail; Grande, Gunn
Abstract : Background: Barriers and facilitators to implementation of comprehensive person-centred assessment and support within palliative care have been identified (Ewing & Grande, 2018). To address the challenges, an online toolkit was developed to provide organisations with structured implementation guidance for the Carer Support Needs Assessment Tool (CSNAT) intervention. However, feedback from practitioners undertaking previous face-to-face CSNAT intervention training and from online toolkit participants highlighted the benefits from follow-up support calls with the opportunity to ask questions and problem solve with their peers, the opportunity to build networks with other organisations completing the training, and having a point of contact to ask questions (Diffin, Ewing, Rowland, Grande, 2018). Currently there is no method for providing this additional support. Project ECHO™ (Extension for Community Healthcare Outcomes) is a tele-mentoring programme which uses video-conferencing to deliver best practice guidance and education from specialists, and case-based learning with opportunities for questions and discussion with peers, and therefore could overcome this gap. Aim: To identify if Project ECHO™ could be used to establish a community of practice and support implementation of the CSNAT intervention. Methods and results: We will draw on the CSNAT implementation evidence base to illustrate the importance of supporting practitioners to gain knowledge about how to use the CSNAT in practice, and enhance their confidence in carrying out assessments. In addition, we will reflect on the implementation support needed at an organisational level, to include practical guidance and opportunities for peer support. In turn, we will highlight how Project ECHO™ could be used to help overcome identified gaps in support through reflection on the core benefits of this methodology to include a curriculum identified by the network participants themselves, case-based learning, and the ability to join remotely. Conclusion: This paper identifies how Project ECHO™ could be utilised to establish a community of practice to support implementation and embedding of comprehensive person-centred assessment and support for family carers into everyday practice.